The genus Matricaria L. (Asteraceae) in Turkey - Inceer, Huseyin (Biodiversity: Research and Conservation, 2019)
In this study, a report on the genus Matricaria in Turkey is provided based on floristic studies. Previously recorded taxa are compared with new ones from our collections. Four taxa of Matricaria in Turkish flora are recognized: M. aurea, M. chamomilla var. chamomilla, M. chamomilla var. recutita and M. matricarioides. On the other hand, M. chamomilla var. coronata is an erroneous record for the flora of Turkey. Diagnostic morphological characters together with data on phenology, habitat and distribution as well as dichotomous keys for Matricaria taxa are presented. Proportions of various phytogeographical elements of Matricaria taxa in Turkey are provided.